Operator-independent high-throughput polymerization screening based on automated inline NMR and online SEC - Van Herck, Joren; Abeysekera, Iyomali; Buckinx, Axel-Laurenz; Cai, Kewei; Hooker, Jordan; Thakur, Kirti; Van de Reydt, Emma; Voorter, Pieter-Jan; Wyers, Dries; Junkers, Tanja (Digital discovery, 2022)
Traditional protocols for high-throughput screening and experimentation are inherently time-consuming and cost-ineffective. Herein, we present a continuous flow-based automated synthesis platform that allows for rapid screenings of polymerizations. The platform uses online monitoring to acquire real time analytic data. Software is developed to guide data acquisition, and most importantly, to carry out reactions and their analysis autonomously. Further algorithms automatically detect experimental inaccuracies, and clean data. Data is aggregated and provided directly in a machine-readable manner, opening pathways towards creation of ‘big data’ sets for kinetic information that is independent of individual user biases and systematic errors. We demonstrate this platform on reversible-addition fragmentation chain transfer polymerization (RAFT). 8 different operators, ranging from PhD students with no prior experience in flow chemistry or RAFT polymerization, up to the professor of the research group created in this way a coherent dataset spanning 8 different monomers containing 3600 NMR spectra and about 400 molecular weight distribution analyses. Coherence of the dataset is demonstrated by reducing key kinetic information that describe the whole covered reaction space in a single parameter.